COST–BENEFIT ANALYSIS OF IMPLEMENTING BILINGUAL PROGRAMS IN RURAL PRIMARY SCHOOLS - Sultanova Shohistaxon Shavkatovna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Annotation: This paper examines the economic feasibility and potential long-term returns of implementing bilingual education programs in rural primary schools. It analyzes both the short-term costs — such as teacher training, curriculum development, and production of bilingual learning materials — and the long-term benefits, including improved literacy, reduced dropout rates, increased employability, and enhanced social cohesion. Using a cost–benefit framework, the study draws on international case studies and empirical data to evaluate how bilingual education can contribute to human capital formation and rural development. The findings suggest that while initial investments are significant, the socio-economic returns over time far outweigh the costs, making bilingual education a viable policy for sustainable rural advancement.